2019
DOI: 10.25080/majora-7ddc1dd1-013
|View full text |Cite
|
Sign up to set email alerts
|

PMDA - Parallel Molecular Dynamics Analysis

Abstract: MDAnalysis is an object-oriented Python library to analyze trajectories from molecular dynamics (MD) simulations in many popular formats. With the development of highly optimized MD software packages on high performance computing (HPC) resources, the size of simulation trajectories is growing up to many terabytes in size. However efficient usage of multicore architecture is a challenge for MDAnalysis, which does not yet provide a standard interface for parallel analysis. To address the challenge, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…RMSD's of backbone atoms, all binding site residues and ligand atoms were calculated to assess the stability of the Zn-bound structures. Radial distribution functions between the zinc ion and binding site ligand atoms were compared with the distances from crystal structures using RDF.InterRDFs in Parallel MD Analysis (PMDA) (Fan et al, 2019). Development of antibody fragments that recognize YiiP.…”
Section: Classical Force Field Model For Zn(ii) Ionsmentioning
confidence: 99%
“…RMSD's of backbone atoms, all binding site residues and ligand atoms were calculated to assess the stability of the Zn-bound structures. Radial distribution functions between the zinc ion and binding site ligand atoms were compared with the distances from crystal structures using RDF.InterRDFs in Parallel MD Analysis (PMDA) (Fan et al, 2019). Development of antibody fragments that recognize YiiP.…”
Section: Classical Force Field Model For Zn(ii) Ionsmentioning
confidence: 99%
“…In other studies, better scaling was observed for analysis tasks that were more compute‐intensive than the RMSD calculation, such as a radial distribution function calculation, 26,52 that is, analysis tasks that could be characterized as compute‐bound. Such behavior is expected, as the contribution from the parallel part of the program that requires neither I/O nor communication is increased.…”
Section: Computational Experimentsmentioning
confidence: 91%
“…Although straggler tasks are a common challenge arising in parallel analysis and are well known in the data analysis community (see Section 2.1), there is, to our knowledge, little discussion about this problem in the biomolecular simulation community. Our own experience with a MapReduce approach in MDAnalysis 24,26 suggested that stragglers might be a somewhat under‐appreciated problem. Therefore, in the present work we wanted to better understand requirements for efficient parallel analysis of MD trajectories in MDAnalysis , but to also provide more general guidance that could benefit developments in other libraries.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, we are particularly interested in the development of Parallel MDAnalysis (PMDA). 66 PMDA is based on MDAnalysis and uses Dask to parallelise the analysis modules. 67 The analysis classes inherit a modified abstract base class that is specifically designed to make the parallelisation straightforward.…”
Section: Benchmarkingmentioning
confidence: 99%